Reliability of self-reported weight and height among State bank employees - Dóra Chor; Evandro da Silva Freire Coutinho; Ruy Laurenti
INTRODUCTION: Self-reported weight and height were compared with direct measurements in order to evaluate the agreement between the two sources. METHOD: Data were obtained from a cross-sectional study on health status from a probabilistic sample of 1,183 employees of a bank, in Rio de Janeiro State, Brazil. Direct measurements were made of 322 employees. Differences between the two sources were evaluated using mean differences, limits of agreement and intraclass correlation coefficient (ICC). RESULTS AND CONCLUSIONS: Men and women tended to underestimate their weight while differences between self-reported and measured height were insignificant. Body mass index (BMI) mean differences were smaller than those observed for weight. ICC was over 0.98 for weight and 0.95 for BMI, expressing close agreement. Combining a graphical method with ICC may be useful in pilot studies to detect populational groups capable of providing reliable information on weight and height, thus minimizing resources needed for field work.